High manganese concentrations in rocks at Gale crater, Mars. Issue 16 (25th August 2014) - Lanza, Nina L.; Fischer, Woodward W.; Wiens, Roger C.; Grotzinger, John; Ollila, Ann M.; Cousin, Agnes; Anderson, Ryan B.; Clark, Benton C.; Gellert, Ralf; Mangold, Nicolas; Maurice, Sylvestre; Le Mouélic, Stéphane; et al.
Abstract The surface of Mars has long been considered a relatively oxidizing environment, an idea supported by the abundance of ferric iron phases observed there. However, compared to iron, manganese is sensitive only to high redox potential oxidants, and when concentrated in rocks, it provides a more specific redox indicator of aqueous environments. Observations from the ChemCam instrument on the Curiosity rover indicate abundances of manganese in and on some rock targets that are 1–2 orders of magnitude higher than previously observed on Mars, suggesting the presence of an as‐yet unidentified manganese‐rich phase. These results show that the Martian surface has at some point in time hosted much more highly oxidizing conditions than has previously been recognized.